Penurunan Jumlah Cacat Dan Biaya Bahan Baku Dengan Metode Responsesponsse Surface - Muhammad Lukman; Ahmad Zubaid Firdaus; Rahadian Galih (Department Industrial Engineering, University of Muhammadiyah Malang, 2013)
CV. Indah Cemerlang is a company for building material which produces paving stone. The company often changes the raw materials composition which is affected by cost of raw materials. Change of the raw materials composition makes product quality lower. Therefore, a study should be conducted in order to identify control factors influencing on defect responsse by using Responsse Surface method. Responsse surface method used in this research consists of two stages. First stage, called orde 1, is dealing with screening and second stage, called orde 2, is dealing with optimization. The result of orde 1 shows that the raw materials composition influencing on defect responsse are cement volume and gray stone. According to the result of second stage, the experiment is conducted to determine optimal amount of raw materials composition. Optimal amount of the raw materials composition are 20 liters of water, 47 kilograms of cement, 120 kilograms of sand, and 10.45 doses of gray stone, with value of defect responsse 5.08%. Applying proposed composition can decrease cost of raw material by Rp 49,33 per pallet and cost of poor quality by 47.60 per week.